Manifestations of linguistic specificity in the writings of some contemporary Algerian linguists - bareche, khalissa; ammari, Azzddine (El Omda in Linguistics and Discourse Analysis, 2024)
Linguistic privacy is the feature that we find in a linguistic researcher without another, this specificity is prominent in the writing of the Algerian linguists, and it had a prominent role in the intensification of linguistic visions in both its theoretical and practical aspects, of which: The uniqueness of some Algerian linguistic researchers with bold research breakthroughs that contributed to the development of linguistic research in this country, and The epistemological fanaticism of some Algerian linguists researchers and the freedom from collective restrictions in the formulation of terminology, which generated astonishment among the reader in receiving knowledge linguistic